(untitled) (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
Accessibility to public facilities is a crucial aspect of improving people’s quality of life; however, their distribution is often uneven across regions. This study developed a local WebGIS application to analyze the spatial proximity of public facilities by utilizing the ST_DWithin function in PostGIS, combined with Leaflet Routing Machine and systematic validation against Google Maps. Spatial data were obtained from official agencies and covered transportation, public services, commercial, and recreational categories within the administrative boundaries of Central Java Province. Proximity analysis was conducted within a 5 km radius, representing a reasonable travel distance for communities to access public services, and the results were visualized in an interactive WebGIS interface. Validation was performed using 30 origin–destination pairs, showing a mean absolute percentage error of 11.3% for distance and 28.2% for travel time, with all distance deviations remaining within acceptable tolerance levels. The novelty of this study lies in the integration of local spatial data analysis using ST_DWithin with actual route computation via LRM, along with a systematic quantitative comparison against Google Maps within the Central Java context, an approach that has been rarely applied in previous accessibility studies in Indonesia. Practically, the system can be used by local governments to identify spatial inequalities, support transportation and spatial planning, and enhance the independence of local spatial data management.